2013
DOI: 10.4172/2155-9899.1000178
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and Candidal Colonisation in Denture Associated Stomatitis

Abstract: Denture stomatitis (DS) is an inflammatory oral condition affecting most frequently the palatal mucosa covered by the fitting surface of a denture. The aim of this study was to determine the local cytokine profile generated in DS, as well as the level and identity of Candida involved. Palatal inflammation was determined by clinical indices in 93 upper denture-wearing subjects (42 with DS). The level of selected cytokines in palatal fluid was measured by cytometric bead array. Grouping of the cytokines associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…We have recently demonstrated that higher TNF α production and inflammation in oral mucosa was associated with C. albicans infection in denture stomatitis [18]. Following sufficient control of C. albicans colonisation in such patients, a reduction of M1 macrophage activity using IL-34 might therefore be beneficial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that higher TNF α production and inflammation in oral mucosa was associated with C. albicans infection in denture stomatitis [18]. Following sufficient control of C. albicans colonisation in such patients, a reduction of M1 macrophage activity using IL-34 might therefore be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages are normally found at sites of inflammation of the skin and are associated with GM-CSF expression by infiltrating and reactive CD4 + T cells, resulting in higher levels of TNF α [1, 16, 17]. We have also shown that denture stomatitis involving C. albicans is associated with higher levels of TNF α in fluids from the oral palatal mucosa [18]. …”
Section: Introductionmentioning
confidence: 99%